Pengaruh Praktik Pencegahan Korupsi dan Profitabilitas terhadap Penghindaran Pajak dengan Hubungan Risiko Bisnis sebagai Pemoderasi - Dewa Ayu Rai Istri Mahottami; I Gusti Ayu Purnamawati; I Putu Gede Diatmika (Universitas Hamzanwadi, 2026)
This study aims to empirically prove the effect of corruption prevention practices on tax avoidance, the effect of profitability on tax avoidance, the effect of profitability on tax avoidance with business risk as a moderator, the effect of corruption prevention practices on tax avoidance with business risk as a moderator. The population in this study were 44 mining companies listed on the Indonesia Stock Exchange and published on the website www.idx.com in the 2020-2024 period. The number of samples was determined using purposive sampling so that the number of samples was 42 companies and 5 years of observation so that the number of samples was 210 samples. This study used linear regression analysis with E-Views software. The results showed that corruption prevention practices did not have a significant effect on tax avoidance, profitability had a significant effect on tax avoidance, business risk did not moderate the relationship between corruption prevention practices on tax avoidance, and business risk moderated the effect of profitability on tax avoidance.